Spores of Clostridium difficile clinical isolates display a diverse germination response to bile salts - Heeg, Daniela; Burns, David A.; Cartman, Stephen T.; Minton, Nigel P. (Public Library of Science, 2012)
Clostridium difficile spores play a pivotal role in the transmission of infectious diarrhoea, but in order to cause disease spores must complete germination and return to vegetative cell growth. While the mechanisms of spore germination are well understood in Bacillus, knowledge of C. difficile germination remains limited. Previous studies have shown that bile salts and amino acids play an important role in regulating the germination response of C. difficile spores. Taurocholate, in combination with glycine, can stimulate germination, whereas chenodeoxycholate has been shown to inhibit spore germination in a C. difficile clinical isolate. Our recent studies of C. difficile sporulation characteristics have since pointed to substantial diversity among different clinical isolates. Consequently, in this study we investigated how the germination characteristics of different C. difficile isolates vary in response to bile salts. By analysing 29 isolates, including 16 belonging to the BI/NAP1/027 type, we show that considerable diversity exists in both the rate and extent of C. difficile germination in response to rich medium containing both taurocholate and glycine. Strikingly, we also show that although a potent inhibitor of germination for some isolates, chenodeoxycholate does not inhibit the germination, or outgrowth, of all C. difficile strains. Finally, we provide evidence that components of rich media may induce the germination of C. difficile spores, even in the absence of taurocholate. Taken together, these data suggest that the mechanisms of C. difficile spore germination in response to bile salts are complex and require further study. Furthermore, we stress the importance of studying multiple isolates in the future when analysing the nutrients or chemicals that either stimulate or inhibit C. difficile spore germination.